Expanding access to coronary artery bypass surgery: who stands to gain?. Issue 2 (February 1995) - Kee, F.; Gaffney, B.; Canavan, C.; Little, J.; McConnell, W.; Telford, A. M.; Watson, J. D.
Abstract : OBJECTIVE–To determine the perceptions of general practitioners (GPs) about the benefits of coronary artery bypass surgery, in terms of gains in life expectancy, for different groups of patients. DESIGN–A questionnaire survey of all GPs in Northern Ireland. SETTING–A survey conducted collaboratively by the departments of public health medicine in each of the four health boards in the province, serving a total population of 1.5 million. MAIN OUTCOME MEASURES–The median and mean gain in life expectancy perceived by groups of doctors for smoking and non-smoking male and female 55 year old patients. The percentage of 50 year old and 70 year old non-smoking patients considered likely to have their lives extended with bypass surgery. Differences were assessed using the Mann-Whitney U test for unpaired samples and the Wilcoxon signed rank tests for paired. RESULTS–541 GPs replied (response rate 56%). The median (and mean) perceived gain in life expectancy after cardiac surgery for non-smoking 55 year old subjects was 120 (104) months for men and 120 (112) months for women (z = 6.42; P < 0.0001; Wilcoxon signed rank test). For male and female smokers of the same age, the perceived gains were 48 (47) and 60 (52) months respectively (z = 6.72; P < 0.0001; Wilcoxon signed ranks test), both figures being significantly different than for non-smokers. The median (and mean) percentage of patients that the doctors considered would have their lives extended by bypass surgery was 70 (64) of every 100 "young" patients and 40 (42) of every 100 "old" patients, (z = 16.2; P < 0.0001). CONCLUSIONS–These results point to a significant overestimation of the benefits of coronary artery bypass surgery by GPs in Northern Ireland and to a need to develop guidelines for referral.